2022
DOI: 10.3390/w14091489
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Annual and Seasonal Variability of Flows: Delivering Climate-Smart Environmental Flow Reference Values

Abstract: Environmental flow (eflow) reference values play a key role in environmental water science and practice. In Mexico, eflow assessments are set by a norm in which the frequency of occurrence is the managing factor to integrate inter-annual and seasonal flow variability components into environmental water reserves. However, the frequency parameters have been used indistinctively between streamflow types. In this study, flow variability contributions in 40 rivers were evaluated based on hydrology, climate, and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…In summary, this standard recognizes that the seasonal and interannual variability of the natural hydrological regime, in terms of attributes such as magnitude, frequency, duration, timing, and rate of change, as well as its components of ordinary and extraordinary flows, are essential for the development of ecological processes, functions, and ecosystem services. It also acknowledges that as water resources are used and the regime is modified, the biological-ecological condition of the ecosystem degrades [13,[17][18][19]. Apart from the various environmental flow assessment methods used for water planning and management or research purposes (e.g., hydrological, ecohydrological, habitat simulation, or holistic approaches) [16,36,37], the environmental flows are assessed based on the assignment of environmental or management objectives.…”
Section: Variablementioning
confidence: 99%
See 3 more Smart Citations
“…In summary, this standard recognizes that the seasonal and interannual variability of the natural hydrological regime, in terms of attributes such as magnitude, frequency, duration, timing, and rate of change, as well as its components of ordinary and extraordinary flows, are essential for the development of ecological processes, functions, and ecosystem services. It also acknowledges that as water resources are used and the regime is modified, the biological-ecological condition of the ecosystem degrades [13,[17][18][19]. Apart from the various environmental flow assessment methods used for water planning and management or research purposes (e.g., hydrological, ecohydrological, habitat simulation, or holistic approaches) [16,36,37], the environmental flows are assessed based on the assignment of environmental or management objectives.…”
Section: Variablementioning
confidence: 99%
“…Although similar environmental flow estimations are currently available and could inform implementation progress against water scarcity, they are global-scale-model-derived, display significant gaps or inconsistencies in arid, and semiarid climates, and limit confidence in their relevance in countries like Mexico [43][44][45]. This assessment is based on systematic analyses of outcomes reported in scientific literature that have demonstrated consistency between hydrological, ecohydrological, and holistic methods generated in nearly 300 case studies in Mexico [13,[17][18][19].…”
Section: Water Reserves For Water Planning Based On Reference Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Variability tests and PCA method were used. As a result, seasonality and variability of river flows were evaluated in terms of climate-smart environmental flow reference values [15]. Eng et al identified five distinct seasonality patterns in the zero-flow events in the United States and strong correlation patterns with historical variations in climate [16].…”
Section: Introductionmentioning
confidence: 99%